TeO2–SiO2–B2O3 glasses doped with CeO2 for gamma radiation shielding and dosimetry application. (November 2022) - D'Souza, Ashwitha Nancy; Sayyed, M.I.; Karunakara, Naregundi; Al-Ghamdi, Hanan; Almuqrin, Aljawhara H.; Elsafi, M.; Khandaker, Mayeen Uddin; Kamath, Sudha D.
Abstract: Bismuth borosilicate glasses doped with 0.5 mol% of CeO2 and increasing concentration of TeO2 (0–40 mol%) are synthesized by melt quench method with 1250 0 C melting temperature, then coded as BiTe glasses. Theoretical values of parameters related gamma radiation shielding such as linear attenuation coefficient (LAC) and mean free path (MFP) are determined from Phy-X/PSD software in the radiation energy range of 0.015–15 MeV. We have achieved greater density value of around 5 gcm −3 and highest set of LAC values 314–0.2 cm −1 for BiTe-40 glass along with lowest range 0.002–3.8 cm of HVL thickness. On gamma irradiation, there was a notable enhancement in thermoluminescence (TL) intensity for TeO2 content greater than 30 mol% due to increase in density of trap centres. CeO2 incorporation has also contributed to increasing density of trap centres. The kinetic parameters were evaluated with the help of glow curve deconvolution technique from which the calculated activation energy was highest (1.652 eV) for BiTe-40 glass with longer lifetime (6.34 × 10 6 years) of charges trapped in high temperature region of 559 K. Highlights: Among synthesized glasses, BiTe-40 glass exhibited maximum density 5.087 g/cm 3 . BiTe-40 produced small HVL of 3.81 cm at 6 MeV as maximum value. For 3 kGy dose, TL intensity increases drastically for 30 and 40mol% addition of TeO2 . BiTe-40 can be promising candidate for TLD application with highest activation energy of 1.652eV. The charges trapped at 559K have longest lifetime of 6.34 × 10 6 years.